Plantas medicinales más utilizadas por los usuarios del Hospital Oncológico de Solca de Loja, para controlar náusea y vómito postquimioterapia 2014 - Bravo Robles, María Isabel (2015)
The present research was to determine which plants are used to control nausea and vomiting in patients receiving chemotherapy in the Oncology Hospital SOLCA, so that the problem arises from the concern to check the most used plants for greater control of these symptoms. From the field of oncology it has been taken into account that patients receiving chemotherapy more frequently encountered side effects are nausea and vomiting. Since these symptoms affect quality of life of the patient, increase the risk of nutritional deterioration. The method used was the descriptive study was composed of patients with different diagnoses who received chemotherapy treatment. In a total of 360; selected a sample of 110 patients. The questionnaire, the same as were applied to each patient, in order to gather information that represents the fulfillment of the objectives was used for data collection. In the present investigation it was found that a high percentage of patients used ginger, chamomile, matico, lemon balm, mint and basil to relieve nausea and vomiting; besides patients receiving chemotherapy treatment in cancer Solca Hospital of Loja, medicinal plants report that they consume to control nausea and vomiting are mostly other places, while patients frequently use fresh stem of the plant as a supplement to relieve nausea and vomiting; Although medications are the main way to treat, other treatments such as relaxation techniques, acupuncture and acupressure, as well as healthy eating and medicinal plants, whereas the effects of these plants is significant. Key words: medicinal plants, nausea, vomiting and chemotherapy